2012
DOI: 10.1002/ijc.27798
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression and epigenetic discovery screen reveal methylation of SFRP2 in prostate cancer

Abstract: Aberrant activation of Wnts is common in human cancers, including prostate. Hypermethylation associated transcriptional silencing of Wnt antagonist genes SFRPs (Secreted Frizzled-Related Proteins) is a frequent oncogenic event. The significance of this is not known in prostate cancer. The objectives of our study were to (i) profile Wnt signaling related gene expression and (ii) investigate methylation of Wnt antagonist genes in prostate cancer. Using TaqMan Low Density Arrays, we identified 15 Wnt signaling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…Specifically, studies in several malignances have demonstrated downregulation of sFRP2 via epigenetic promoter hypermethylation, suggesting a possible role as a tumor suppressor [26, 27]. However, recently reports provide evidence that sFRP2 can enhance tumor aggressiveness or progression in several cancers, including melanoma, renal cancer, angiosarcoma, and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies in several malignances have demonstrated downregulation of sFRP2 via epigenetic promoter hypermethylation, suggesting a possible role as a tumor suppressor [26, 27]. However, recently reports provide evidence that sFRP2 can enhance tumor aggressiveness or progression in several cancers, including melanoma, renal cancer, angiosarcoma, and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, hyperactive Wnt signalling has been linked with androgen-independent growth through crosstalk with the androgen receptor [34], development of bone metastasis [35], and self-renewal of prostate cancer stem cells [36]. The heterogeneity of prostate cancer is also due to a broad spectrum of genetic and epigenetic abnormalities.…”
Section: Prostate Cancermentioning
confidence: 99%
“…To understand the crucial role of Wnt signalling pathway in prostate cancer, Perry et al [36] examined the role of Wnt antagonists (SFRPs) in prostate cancer cell lines, namely, LNCaP, PC-3, DU145, and 22Rv1, on a set of 20 tumour specimens obtained from men undergoing radical prostatectomy. It was reported that SFRP2 was methylated in 70% of tumour specimens and SFRP5…”
Section: Prostate Cancermentioning
confidence: 99%
“…As previously reported, the expression of SFRP2 was down-regulated by methylation in cancer [14, 15]. Because calcium signaling was reduced by defect of Sfrp2 , down-regulation of SFRP2 is assumed to impair the calcium signal transduction in each tissue or cell.…”
Section: Discussionmentioning
confidence: 68%